Principles and practice of public health surveillance - Lee, Lisa M. (New York ; Oxford : Oxford University Press, 2010)
Public health surveillance is the systematic, ongoing assessment of the health of a community, based on the collection interpretation & use of health data. Surveillance provides information necessary for public health decision making & interventions.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 9, 2010).
Keywords: Public health surveillance